Sorption of europium on diatom biosilica as model of a "green" sorbent for f-elements. (March 2021) - Kammerlander, Kaitlin Kim Karlotta; Köhler, Lydia; Huittinen, Nina; Bok, Frank; Steudtner, Robin; Oschatz, Cathleen; Vogel, Manja; Stumpf, Thorsten; Brunner, Eike
Abstract: Removing f -elements from anthropogenically contaminated sites is a challenging, but ecologically important task. Some of these elements are not only radioactive, but also chemically toxic and can spread through various pathways in the environment. The present work investigates f -element sorption on biogenic silica, which may be a promising "green" material for remediation. Commercially available diatomaceous earth (DE) and the cleaned cell walls of the diatom species Stephanopyxis turris ( S.t. ) and Thalassiosira pseudonana ( T.p. ) are compared with artificial mesocellular foam (MCF) as porous silica reference material. Trivalent europium was chosen as model sorptive for chemically similar trivalent actinides. Accordingly, Eu(III) in concentrations of 10 −3  M and 10 −5  M was sorbed on the four silica materials at varying pH values. The zeta potentials of the implemented sorbents under the same conditions were determined. In addition, the sorption reaction and the aqueous speciation of Eu(III) in the (bio)silica suspensions were modeled using the Diffuse Double Layer (DDL) model. With time-resolved laser-induced fluorescence spectroscopy (TRLFS), two different uptake mechanisms were discerned, surface adsorption and incorporation/precipitation. Graphical abstract: Image 1 Highlights: The sorption of Eu(III) on biogenic and non-biogenic silica was investigated. Sorbates were characterized with ICP-OES, SEM/EDX, TRLFS, and SCM. Different Eu species could be discerned coinciding with the sorbent's SSA. Origin and type of impurity elements of the silica influences the sorption.